URINARY TRACT INFECTIONS AND THEIR CAUSATIVE PATHOGENS (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
Urinary tract infections (UTIs) are among the most common pathological conditions in urology, affecting individuals of various age groups and potentially leading to serious complications. This article provides a comprehensive analysis of the etiological factors, microbiological characteristics, and pathogenesis of UTIs, as well as the causative microorganisms, based on current scientific evidence. Diagnostic criteria are established using modern laboratory and instrumental methods and are discussed in correlation with relevant clinical and hygienic recommendations. Furthermore, contemporary treatment strategies for microorganism-induced urinary tract diseases are reviewed, including the principles of antibacterial therapy and the significance of symptomatic and pathogenetic approaches.